Development of Interactive Educational Snakes and Ladders Media (LANTERA) to Improve Science and Social Studies (IPAS) Learning Outcomes on Human Digestive System Material - Lailatun Ni'mah; Aan Widiyono (Universitas Lambung Mangkurat, 2026)
Teaching IPAS material on the human digestive system in grade V of elementary school (SD) faces obstacles because the abstract concept of digestive organs is difficult for students to understand without concrete media. This research developed the Interactive Educational Snakes and Ladders (LANTERA) media that meets the criteria of being feasible, practical, and capable of improving students' cognitive learning outcomes based on Bloom's Taxonomy (C3–C6). The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 33 grade V students of SDN 1 Purwogondo using a total sampling technique. Research instruments included observation guidelines, interviews, expert validation sheets, pre-test and post-test questions, as well as teacher and student response questionnaires. Validation results showed the media met the feasibility criteria with a score of 96.43% from media experts and 84.5% from material experts. The increase in learning outcomes was measured using N-Gain with an average of 0.6187 (medium category), with a distribution of 48.5% of students in the high category, 39.4% medium, and 12.1% low. Teacher responses reached 98% and student responses 92.6%, indicating very high practicality. LANTERA media is proven to be able to improve cognitive learning outcomes through the integration of visualization, gamification, and collaborative learning, so it can be an alternative for game-based learning for abstract material in elementary schools.